Targeting Bromodomain and Extraterminal Proteins in Breast Cancer - Sahni, Jennifer M. (Pharmacol Res, 2017)
Breast cancer is a collection of distinct tumor subtypes that are driven by unique gene expression profiles. These transcriptomes are controlled by various epigenetic marks that dictate which genes are expressed and suppressed. During carcinogenesis, extensive restructuring of the epigenome occurs, including aberrant acetylation, alteration of methylation patterns, and accumulation of epigenetic readers at oncogenes. As epigenetic alterations are reversible, epigenome-modulating drugs could provide a mechanism to silence numerous oncogenes simultaneously. Here, we review the impact of inhibitors of the Bromodomain and Extraterminal (BET) family of epigenetic readers in breast cancer. These agents, including the prototypical BET inhibitor JQ1, have been shown to suppress a variety of oncogenic pathways while inducing minimal, if any, toxicity in models of several subtypes of breast cancer. BET inhibitors also synergize with multiple approved anti-cancer drugs, providing a greater response in breast cancer cell lines and mouse models than either single agent. The combined findings of the studies discussed here provide an excellent rationale for the continued investigation of the utility of BET inhibitors in breast cancer.